KEEFEKTIFAN MODEL TEAMS GAMES TOURNAMENT BERBANTU MEDIA MONOTIK TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS IV - Sari, Dwi Fitri; Wijayanti, Arfilia; Artharina, Filia Prima (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2020)
The low student learning outcomes in thematic learning due to the lack of model variation in the used of instructional media. The purposed of this research was to study the effectiveness of the Teams Games Tournament (TGT) assisted by monotic media to learning otcomes in the sub-theme Aku dan Cita-citaku. This type of research was quantitative with a pre-experimental design. The form of research is one group pretest-postttest design. The research population was all grade IV students at SDN Batu 02 Demak. Samples types were 22 fourth grade students with the saturated sampling technique. Research data obtained trough research instrument, pretest, postttest, documentation, and observation sheet. Based on the results of the analysis of the data obtained tcount =5.622. then compared to the price ttable at db=21 wit a level of ?=0.05 is 2.080. so,Ho was refused and Ha was accepted. The mastery of classical learning in the posttest has reached 75%, it was concluded that the Teams Games Tournament (TGT) model assisted by monotic media was effective of the learning outcomes of grade IV students in the sub-theme of Aku dan Cita-citaku.